PENGARUH REWARD TERHADAP MOTIVASI BELAJAR SISWA - Sarita Cyntia Aljena; Kadek Dewi Wahyuni Andari; Kartini Kartini (Universitas Borneo Tarakan, 2020)
Abstract:The study is aimed to determine the effect of giving rewards to motivate students of class V at 033 elementary school in Tarakan. The research is conducted on the date of January 27th until February 24th 2020 at 033 elementray school in Tarakan.The population in this study were all fifth grade students at 033 elementary school in Tarakan. Sample research is numbered 108th students were taken to the tehnique of sampling saturated taking samples when all members of the population used as a sample. Mechanical collection of data in the study is using questionnaires, interviews are not structured, documentation and technical analysis of the data used is analysis of regression linear simple with the help of program software SPSS 21.0 for windows.The results of the analysis of the research data showed that there was a significant influence between giving rewards to students’ learning motivation in grade V 033 elementray school in Tarakan with a regression equation equation Y= 27,429 + 0.7 04 X. Where the significance of the effect was shown by fcount 48.326 ftable 3.93. While through the T test obtained the value tcount 6.954 ttable 1.982. It is shows that there are significant between giving a reward to the motivation to learn student class V at 033 elementary school in Tarakan.From the results of the test hypotheses obtained rcount 0.560 rTable 0.187. Shows that the magnitude of the effect of giving reward to the motivation to learn the student is at 31,3%, while the remaining 68,7% are influenced by variables other.Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh pemberian reward terhadap motivasi belajar siswa kelas V SDN 033 Tarakan. Penelitian ini dilaksanakan pada tanggal 27 Januari s.d 24 Februari 2020 di SDN 033 Tarakan.Populasi dalam penelitian ini adalah seluruh siswa kelas V SDN 033 Tarakan. Sampel penelitian ini berjumlah 108 siswa yang diambil dengan Tekniksampling jenuh pengambilan sampel bila semua anggota populasi digunakan sebagai sampel. Teknik Pengumpulan data dalam penelitian ini menggunakan angket, wawancara tidak terstruktur, dokumentasi dan teknik analisis data yang digunakan adalah analisis regresi linier sederhana dengan bantuan program Software SPSS 21.0 for windows.Hasil analisis data penelitian menunjukkan terdapat pengaruh signifikan antara pemberian reward terhadap motivasi belajar siswa kelas V SDN 033 Tarakan dengan persamaan regresi Y = 27,429 + 0,704X. dimana signifikansi hubungan ditunjukkan oleh fhitung 48,362 ftabel 3,93. Sedangkan melalui uji t diperoleh nilai thitung 6,954 ttabel 1,982. Hal tersebut menunjukkan bahwa terdapat pengaruh antara pemberian reward terhadap motivasi belajar siswa kelas V SDN 033 Tarakan.Dari hasil uji hipotesis diperoleh rhitung 0,560 rtabel 0,187, menunjukkan bahwa besarnya pengaruh pemberian reward terhadap motivasi belajar siswa adalah sebesar 31,3 % sedangkan sisanya 68,7 % dipengaruhi oleh variabel lain. Abstract:The study is aimed to determine the effect of giving rewards to motivate students of class V at 033 elementary school in Tarakan. The research is conducted on the date of January 27th until February 24th 2020 at 033 elementray school in Tarakan.The population in this study were all fifth grade students at 033 elementary school in Tarakan. Sample research is numbered 108th students were taken to the tehnique of sampling saturated taking samples when all members of the population used as a sample. Mechanical collection of data in the study is using questionnaires, interviews are not structured, documentation and technical analysis of the data used is analysis of regression linear simple with the help of program software SPSS 21.0 for windows.The results of the analysis of the research data showed that there was a significant influence between giving rewards to students’ learning motivation in grade V 033 elementray school in Tarakan with a regression equation equation Y= 27,429 + 0.7 04 X. Where the significance of the effect was shown by fcount 48.326 ftable 3.93. While through the T test obtained the value tcount 6.954 ttable 1.982. It is shows that there are significant between giving a reward to the motivation to learn student class V at 033 elementary school in Tarakan.From the results of the test hypotheses obtained rcount 0.560 rTable 0.187. Shows that the magnitude of the effect of giving reward to the motivation to learn the student is at 31,3%, while the remaining 68,7% are influenced by variables other.Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh pemberian reward terhadap motivasi belajar siswa kelas V SDN 033 Tarakan. Penelitian ini dilaksanakan pada tanggal 27 Januari s.d 24 Februari 2020 di SDN 033 Tarakan.Populasi dalam penelitian ini adalah seluruh siswa kelas V SDN 033 Tarakan. Sampel penelitian ini berjumlah 108 siswa yang diambil dengan Tekniksampling jenuh pengambilan sampel bila semua anggota populasi digunakan sebagai sampel. Teknik Pengumpulan data dalam penelitian ini menggunakan angket, wawancara tidak terstruktur, dokumentasi dan teknik analisis data yang digunakan adalah analisis regresi linier sederhana dengan bantuan program Software SPSS 21.0 for windows.Hasil analisis data penelitian menunjukkan terdapat pengaruh signifikan antara pemberian reward terhadap motivasi belajar siswa kelas V SDN 033 Tarakan dengan persamaan regresi Y = 27,429 + 0,704X. dimana signifikansi hubungan ditunjukkan oleh fhitung 48,362 ftabel 3,93. Sedangkan melalui uji t diperoleh nilai thitung 6,954 ttabel 1,982. Hal tersebut menunjukkan bahwa terdapat pengaruh antara pemberian reward terhadap motivasi belajar siswa kelas V SDN 033 Tarakan.Dari hasil uji hipotesis diperoleh rhitung 0,560 rtabel 0,187, menunjukkan bahwa besarnya pengaruh pemberian reward terhadap motivasi belajar siswa adalah sebesar 31,3 % sedangkan sisanya 68,7 % dipengaruhi oleh variabel lain.